Research of the system-on-chip-based relay protection technology - Li, Xiaobo; Xi, Wei; Yu, Yang; Yao, Hao (Frontiers in Energy Research, 2023)
The relay protection device is the core equipment that ensures the safe and stable operation of a power grid. With the open access of a large number of distributed generation, DC transmission and electric vehicles, a new deep low-carbon power system dominated by power electronic devices has gradually been formed. It is difficult for the traditional control and protection architecture, methods, and technology to meet the business characteristics and functional requirements of a diversified interaction, agile response, safety, and credibility of the power grid in the future. This paper presents a chip-based relay protection technology based on system-on-chip (SoC), which is described from four aspects, namely, the architectural design of the relay protection SoC, software and hardware cooperative relay protection based on the SoC IP core, experimental verification, and engineering application. The results show that the relay protection SoC proposed in this paper has significantly improved the performance of high-speed data acquisition and interaction through hardware algorithm engine acceleration and software and hardware collaborative computing, which is helpful to realize the local equipment operation and the integration of primary and secondary equipment, shorten the protection action time, and improve the speed, reliability, and stability of relay protection devices.